Vibration Reduction of Semi-Trailer Truck Using MR Dampers: A Fuzzy Logic Control Approach - Kurt, Ilkay; Paksoy, Mahmut; Cetin, Saban; Guclu, Rahmi; Sezer, Semih (IEEE, 2016)
This paper presents a semi-active fuzzy logic control (FLC) strategy designed for a semi-trailer truck suspension system which consists of magnetorheological (MR) damper and linear spring. The objective of the controller is to improve the ride comfort by suppressing the vibrations that result from the road irregularities. The dynamic system is modelled in MATLAB/Simulink simulation environment. Simulations are carried out under standardized random road excitation generated according to ISO 8608 to investigate dynamic behaviour of seven degrees of freedom (DOFs) semi-trailer truck model. The Bouc-Wen model is utilized to characterize the hysteresis phenomenon of the MR dampers. Performance of designed controller is evaluated and the results indicate the effectiveness of the applied control algorithm on the vibration reduction compared to uncontrolled suspension system.
Keywords: fuzzy logic controller; vibration control; semi-active suspension; MR damper; ride comfort; SUSPENSION SYSTEM; Engineering